Criminalization in Regional Regulations: An Analysis of the Formulation of Penal Provisions Based on Law Number 13 of 2022 - widya yoseva; Sistri Wahyuni; Gokma Toni Parlindungan S (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2026)
This study aims to analyze the formulation of criminal provisions in Regional Regulations (Peraturan Daerah) following the enactment of Law Number 13 of 2022 concerning the Second Amendment to Law Number 12 of 2011 on the Formation of Laws and Regulations. The study examines the legal basis, limitations, and principles governing the criminalization process within regional legislation. This research employs normative juridical methods using statutory, conceptual, and comparative approaches. The legal materials consist of primary, secondary, and tertiary legal sources analyzed through qualitative legal interpretation. The study finds that the authority of Regional Governments to formulate criminal sanctions in Regional Regulations is not absolute and must comply with the principles of legality, proportionality, and legal certainty as stipulated in Law Number 13 of 2022. The inclusion of criminal provisions in Regional Regulations should be based on clear delegation of authority, avoid overcriminalization, and align with national criminal law policies and the protection of human rights. This research offers a contemporary analysis of the criminalization policy in Regional Regulations after the enactment of Law Number 13 of 2022 and proposes a conceptual framework for the formulation of regional criminal provisions that are harmonized with the national legal system and constitutional principles.